Peran Kepala Sekolah Dalam Perencanaan Pendidikan Dengan Metode Analisis Input Output Dan Implementasinya Dalam Pengembangan Ekstrakurikuler Tahfidz Di SMP Islam Hegarmanah - Eneng Sumarni; Siti Qomariyah; Eti Robiatl Adawiyah; Ima Muslimatul Amanah; Cucu Sa’adah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The main role of the principal is to plan, implement, assess, guide and train, research (school action research) but there are still many principals who have not implemented educational planning well. This research aims to determine the role of the principal in educational planning using analytical methods. Input Output and Implementation in the Development of Extracurricular Tahfidz at Hegarmanah Islamic Middle School. This research uses qualitative methods. Data will be collected through interviews, observation and documentation analysis. The results of the research show that the strategy carried out by the principal of Hegarmanah Islamic Middle School in implementing educational planning with input and output analysis is to improve the quality of Qur'an tahfidz teachers, students' academic and non-academic achievements. This is implemented by involving teachers in training activities and seminars on extracurricular methods of tahfidz Qur'an, carrying out extracurricular activities, special Muroja'ah and activities, holding Qur'an memorization tests. Meanwhile, improving infrastructure means planning the facilities needed to improve extracurricular tahfidz Qur'an, thereby producing output of students who are able to memorize up to 5 Juz of the Qur'an, as well as increasing students' religious understanding.